The Performance Optimization of Main Engine Injector of MV. Sinar Papua - Tjahjono, Agus; Wiwoho, Boedojo; Afandi, Saifudin (KnE Social Sciences, 2019)
This study was aimed to analyze the performance optimization of the Main Engine injector in MV (Motor Vessel) Sinar Papua. This research used SWOT analysis (Strength, Weakness, Opportunity, and Threat) to formulate the exact strategy in optimizing the injector’s performance. In this study, the data were obtained through questionnaire with random data collection method. Based on the research, the optimization strategy could be done through (1) improving the skill of the engineer in maintaining the injector of the main engine, and (2) establishing sanctions to those who do not carry out injector maintenance according to the procedure of the manual book.